2022
DOI: 10.1038/s41598-022-06606-9
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional deep learning to automatically generate cranial implant geometry

Abstract: We present a 3D deep learning framework that can generate a complete cranial model using a defective one. The Boolean subtraction between these two models generates the geometry of the implant required for surgical reconstruction. There is little or no need for post-processing to eliminate noise in the implant model generated by the proposed approach. The framework can be used to meet the repair needs of cranial imperfections caused by trauma, congenital defects, plastic surgery, or tumor resection. Traditiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 39 publications
0
22
0
1
Order By: Relevance
“…1 ). Following abstract and title screening, 7664 articles were removed, leaving 85 articles for full-text screening.12 articles met the inclusion criteria [ 10 – 21 ] including one identified through hand searching [ 14 ]. All 12 articles were published between 2015 to 2022.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1 ). Following abstract and title screening, 7664 articles were removed, leaving 85 articles for full-text screening.12 articles met the inclusion criteria [ 10 – 21 ] including one identified through hand searching [ 14 ]. All 12 articles were published between 2015 to 2022.…”
Section: Resultsmentioning
confidence: 99%
“…All 12 articles were published between 2015 to 2022. Six studies were identified as unspecific cohort studies [ 10 , 11 , 15 , 18 , 19 , 21 ], five were retrospective cohort studies [ 12 , 14 , 16 , 17 , 20 ], and one was a case study [ 13 ]. 10 studies described approval from a relevant human ethics committee, however this was not mentioned in two articles [ 10 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Específicamente en el manejo de trauma craneofacial, Wang et al (2022) desarrollaron un algoritmo compuesto por dos redes neuronales convolucionales, el cual se entreno y validó, permitiendo detectar y clasificar diferentes tipos de fracturas mandibulares a través de Tomografías Computarizadas. Por otro lado, Wu et al (2022), generaron un modelo de capas neuronales con la capacidad de aprender la distribución espacial del segmento superior de los huesos craneales y utilizar los datos para predecir su geometría completa, para así reconstruir digitalmente los segmentos afectados por trauma y de esa forma generar la prótesis de reemplazo automáticamente e imprimirla de inmediato con la utilización de una impresora 3D, evitando pasos extra como la impresión del biomodelo previamente expuesto.…”
unclassified